Proasf e Paif: a gestão do trabalho social com famílias no município de Suzano do Estado de São Paulo - Silva, Maria Auxiliadora Pereira da (2012)
This study sought to present the social work with families from a program in the city of Suzano called PROASF - Social-Family Guidance and Support Network Program, and PAIF - Program of Comprehensive Care to Family, from the point of view of municipal management. In the course of the research it was presented the historical, economic, social and demographic aspects of Suzano, in particular, the trajectory and the management of social care in the municipality. For the analysis of such programs it was made a historical rescue of most relevant experiments in social work with families, which happened at the federal, state and municipal scope, noting similarities and differences between these experiments. As the implementation of the social work with families was performed by professionals of an entity contracted with the city of Suzano, under the supervision of professionals from government, it was analyzed the relationship between State and Civil Society, presenting the weaknesses and strengths of this partnership. The city of Suzano, while establishing the PROASF, creates a parallelism of actions in social work, with families using resources of the PAIF, without, however, informing families about the existence of the federal program, leading to tensions in the relationship between levels of governmentwork.